2018
DOI: 10.3390/ijms19030852
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Identifies a 140 kb Region of Chromosome 3B Containing Genes Specific to Fusarium Head Blight Resistance in Wheat

Abstract: Fusarium head blight (FHB), mainly caused by Fusarium graminearum, is one of the most destructive fungal diseases of wheat (Triticum aestivum L.). Because of the quantitative nature of FHB resistance, its mechanism is poorly understood. We conducted a comparative transcriptome analysis to identify genes that are differentially expressed in FHB-resistant and FHB-susceptible wheat lines grown under field conditions for various periods after F. graminearum infection and determined the chromosomal distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Starch components, such as amylopectin and amylose, are known to be difficult for the fungus to recycle as a carbon source and for DON production (Oh et al, 2016), unlike sucrose (Jiao et al, 2008;Kawakami et al, 2014), suggesting that the deregulation of the host energy processes at the early stage of the disease could be one of the key factors that determine wheat susceptibility. However, the links are not obvious since many other studies have shown that primary metabolism and especially photosynthesis are extensively rearranged (Long et al, 2015;Biselli et al, 2018;Li et al, 2018;Fabre et al, 2019b). Although this can substantially limit the accumulation of sugars, this could also be seen as a means of constraining the energy requirements necessary to trigger defense mechanisms (Bolton, 2009).…”
Section: Shaping Fhb Susceptibility In the Course Of Grain Developmentmentioning
confidence: 99%
“…Starch components, such as amylopectin and amylose, are known to be difficult for the fungus to recycle as a carbon source and for DON production (Oh et al, 2016), unlike sucrose (Jiao et al, 2008;Kawakami et al, 2014), suggesting that the deregulation of the host energy processes at the early stage of the disease could be one of the key factors that determine wheat susceptibility. However, the links are not obvious since many other studies have shown that primary metabolism and especially photosynthesis are extensively rearranged (Long et al, 2015;Biselli et al, 2018;Li et al, 2018;Fabre et al, 2019b). Although this can substantially limit the accumulation of sugars, this could also be seen as a means of constraining the energy requirements necessary to trigger defense mechanisms (Bolton, 2009).…”
Section: Shaping Fhb Susceptibility In the Course Of Grain Developmentmentioning
confidence: 99%
“…Further studies on wheat have also reported that Fg is able to manipulate wheat cell, in a time-dependent manner, by inducing the reprogramming of pivotal plant biological processes, such as starch and defence metabolisms (Chetouhi et al, 2015(Chetouhi et al, , 2016Erayman et al, 2015). However, most of the in planta analyses performed on this pathosystem have only focused on the plant responses and gained fragmentary information about fungal molecule dynamics (Bönnighausen, Schauer, Schäfer, & Bormann, 2018;Dhokane, Karre, Kushalappa, & McCartney, 2016;Gunnaiah & Kushalappa, 2014;Li et al, 2018). Previous mRNA analyses have already provided new insights into the putative synthesized molecules involved in the molecular dialogue between wheat and its pathogen (Gottwald, Samans, Lück, & Friedt, 2012;Pan et al, 2018;Peyraud et al, 2017;Puri, Yan, Leng, & Zhong, 2016), but transcripts depict only a limited image of the functional cellular products.…”
mentioning
confidence: 99%
“…For example, photosynthesis and the expression of the photosynthesis-related transcripts, such as Cab and RbcS , were reduced in barley- Blumeria graminis f. sp. hordei ( Bgh ) incompatible interaction [ 74 ], and the downregulation of Rubisco and ATPase also occurred under other biotic stresses [ 10 , 29 , 75 ]. However, in some cases, such as in the incompatible interaction between Arabidopsis and P. syringae , the repression of photosynthesis was not correlated with the downregulation of RbcS and Cab transcripts [ 76 ], which may be related to the lack of participation of a majority of plant cells in the defence reaction, thus, the repression of RbcS and Cab cannot be detected in the whole leaves’ RNA.…”
Section: Discussionmentioning
confidence: 99%
“…These defence responses include expression of pathogenesis-related ( PR ) genes and initiation of the hypersensitive response (HR) to restrict biotrophic pathogen growth [ 4 , 8 ]. ETI may also trigger systemic acquired resistance (SAR) responses in distal uninfected tissues [ 9 , 10 ]. Although PTI and ETI responses are triggered by different pathogen-derived molecules, they share several downstream signals, including ROS and phytohormones [ 11 ].…”
Section: Introductionmentioning
confidence: 99%